Tutorials of Visual Graphic Communication Programs for Interior Design - Cho, Yongyeon (Open textbook library., 2021)
This book is for the beginning level of both architecture and interior design students who learn computer graphic communication software. The author developed multiple tutorials to teach three computer graphic applications, AutoCAD, Revit, and Enscape. AutoCAD is an essential computer drafting software which is 2D drawing software. Revit is a Building Information Modeling software, which is 3D based modeling software. Lastly, Enscape is a real-time rendering, animation, and virtual reality plug-in for users' 4D experiences.